2019
DOI: 10.1097/ajp.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Potentials of Preoperative Oral Pregabalin, Intravenous Magnesium Sulfate, and their Combination in Acute Postthoracotomy Pain

Abstract: Objectives: The objective of this study was to investigate the effects of the preoperative combination of oral Pregabalin and intravenous (IV) magnesium sulfate as analgesic adjuvants in postthoracotomy pain. Patients and Methods: One hundred twenty patients with American Society of Anesthesiologists physical status II were allocated randomly into 1 of 4 groups. Group MP received 300 mg pregabalin orally and an IV infusion of magnesium sulfate 50 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…Magnesium is a critical participant in various physiological processes of the body. Therefore, much attention has focused on anesthesiology [ 23 ], resulting in many clinical trials [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], reviews, and meta-analyses [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In particular, the pain attenuation effect of magnesium was investigated to improve the outcomes in surgical patients.…”
Section: Magnesium and Perioperative Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium is a critical participant in various physiological processes of the body. Therefore, much attention has focused on anesthesiology [ 23 ], resulting in many clinical trials [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], reviews, and meta-analyses [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In particular, the pain attenuation effect of magnesium was investigated to improve the outcomes in surgical patients.…”
Section: Magnesium and Perioperative Painmentioning
confidence: 99%
“…A study of liver transplantation showed that the intravenous administration of magnesium sulfate could reduce the requirement of tramadol and the need for mechanical ventilation [ 32 ]. Abdelgalil et al [ 34 ] suggested that the administration of a combined preoperative single dose of pregabalin (300 mg) and magnesium sulfate infusion (50 mg/kg) may be an effective method for enhancing postoperative analgesia and reducing total morphine use after thoracotomy.…”
Section: Magnesium and Perioperative Painmentioning
confidence: 99%
“…A small randomized control trial identified that preoperative administration of pregabalin in conjunction with intravenous magnesium in patients undergoing thoracic surgery significantly decreases postoperative opioid use and pain scores. 22 Other small studies evaluating the efficacy of preoperative administration of pregabalin or gabapentin have echoed similar results. 23,24 It is expected that the next generation guidelines will include some of these approaches for the management of post-thoracic surgery pain.…”
mentioning
confidence: 75%
“…In the case of missing information, we consulted the corresponding authors. We attempted to contact the authors of Salah 2018 for unclear baseline information, but no response was obtained [ 22 ].…”
Section: Methodsmentioning
confidence: 99%